The Position of BPN in Resolving Land Cases in Depok: A Restorative Justice Approach - Nur Hidayati, Maslihati; Suartini, Suartini; Sadino, Sadino; Widarahesty, Yusy; Mumin, Anita (Asian Journal of Social and Humanities, 2025)
Non-penal policies should ideally be regulated as the legal basis for implementing the Land Mafia Prevention and Eradication Task Force Team. Legal certainty refers to the application of laws that are clear, permanent, and consistent. The restorative justice approach will serve as the basis for formulating non-penal policies to resolve land dispute cases in Indonesia. The purpose is to determine the position, role, and responsibilities of BPN in land settlement in Depok City. This research is normative juridical research with the character of prescriptive analysis. The novelty in this research is that the object of the dispute in the BPN Depok area has not involved resolution based on the principles of restorative justice. This study reveals that BPN Depok has achieved significant accomplishments in land case resolution, with a 99.66% dispute resolution rate exceeding national targets. The research demonstrates that BPN's integration of restorative justice principles through mediation, asset certification programs, and technological innovations (BERMATA application) has enhanced both the effectiveness and efficiency of dispute resolution. The findings indicate that BPN's dual role as both mediator and government authority requires careful navigation to maintain stakeholder trust. This study concludes that while restorative justice approaches show promise in land dispute resolution, comprehensive strategies addressing resource constraints, mediator capacity development, and multi-stakeholder collaboration are essential for sustainable implementation. The research contributes theoretically to conflict management literature and practically provides evidence-based recommendations for enhancing BPN's dispute resolution mechanisms in rapidly urbanizing contexts.